A new approach to assessing pterygium progression and volume using SII and anterior segment OCT - Niu, Rui; Jin, Xin; Yan, Zhongyang; Zhao, Ziqi; Fan, Lina; Du, Zhe; Wang, Lifei; Liu, Jingjiang; An, JunSheng; Wang, Xiaoxuan (Frontiers in Medicine, 2026)
PurposeTo compare the clinical manifestations and prognosis of 90 patients with pterygium. The occurrence and progression of pterygium are associated with the systemic immune-inflammatory index (SII) and clinical characteristics. The size of pterygium was assessed by anterior segment phase and anterior segment optical coherence tomography (AS-OCT).MethodsAccording to the pterygium score, the patients were divided into group A, group B, and group C. The evaluation parameters included gender, age, onset time, signs and symptoms of underlying diseases, AS-OCT, Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), Monocyte-to-Lymphocyte Ratio (MLR), and SII values. The postoperative pterygium tissue was weighed. The clinical characteristics of each group were analysed by a nonparametric test and a chi-square test. Ordered logistic regression analysis evaluated the parameters related to pterygium area and volume.ResultsCompared with the control group, the SII, NLR, and MLR values of pterygium patients were significantly increased. The incidence of both eyes in group C was significantly higher than that in groups A and B. The incidence of both eyes and the SII value would affect the severity of pterygium. The SII value was significantly correlated with the area of pterygium progression and weighing volume. The combination of the anterior segment phase and AS-OCT can effectively evaluate the volume of pterygium.ConclusionSII can be used as a biomarker to predict the severity and prognosis of pterygium. Compared with traditional methods, imaging data can better evaluate the progression of pterygium by calculating the volume of pterygium.